The Relationship Between Dietary Patterns And Menstruation With Anemia Status Of Female Adolescents At State SMAN 1 Ngunut, Kabupaten Tulungagung - Eva Agustina Yalestyarini; Heri Saputro; Suci Anggraeni (Journal of Health Science Community, 2026)
Adolescent girls as puberty age group , often lack of  nutrition rich in iron because many of them had restricted food consumption habit. Moreover , the habit of consuming types of snacks that have no nutritional elements rich in iron , was the tendency on the part of young women until they were  suffered with anemic . In Indonesia, the prevalence of anemia in adolescent girls in 2006 , was 28 % . Data collected from Survei Kesehatan Rumah Tangga (SKRT) in 2012 stated that the prevalence of deficiency anemia in adolescent girls aged 10-18 years is 57.1 % ( Depkes RI, 2012) . The results of the current survey of iron tablet supplementation program by Dinas Kesehatan Tulungagung in 2013 , showed that SMA Negeri 1 Ngunut was one of the schools that have students with anemia figure quite high, about 31 % . This study aims to determine the relationship of dietary habits and menstrual status of anemia in adolescent girls in SMA Negeri 1 Ngunut Tulungagung. This research used an analytic correlation with a case control study and a quantitative approach . The sample in this study are young women aged 15 to 17 years a number of 58 met the inclusion criteria consisted of 29 female students in the case group and 29 students in the control group . The sampling technique " Proportional Random Sampling " . The data analized used bivariate analysis using Chi Square test , whereas the multivariate analysis using linear regression with a confidence interval of 95% . Data collected was carried interviews with Food Frequencies Questionnaire ( FFQ ) to the diet, the questionnaire for menstrual and peripheral blood sampling method for anemia the variable using β Hemoque technique. Most of the research subjects in the case group rarely eat animal side dish than the control group often consume most of the animal side dish with more number (65.2 %). Subjects who rarely consume animal side dish had a 3.80 times greater risk of anemia compared to subjects who frequently consume animal side dish ( OR = 3.80 ; 95 % CI 1.30; 5.84 ) . Consumption of vegetable side dishes ( OR = 0.62 ; 95 % CI 0.32 ; 1.62 ) , fruit - fruit ( OR = 0.86 ; 95 % CI ; 0.32 ; 2.51 ) and snacks have a significant relationship but it is not a risk factor for anemia status . The healthy beverage consumption ( OR = 1.51 ; 95 % CI ; 1.30; 3.77 ) and iron supplementation ( OR = 3.39 ; 95 % CI 1.30; 6.84 ) has a significant relationship and a risk factors for anemia especially iron supplements , which subjects who rarely took iron supplements 3 times greater risk of experiencing anemia compared to subjects who often take iron supplements .There was a relationship between dietary habits and anemia status of young women in SMU Negeri 1 Ngunut Tulungagung , where adolescent girls have a frequency rarely consume food sources of heme have a greater risk of having anemia . Statistically not found the relationship between menstrual status of anemia in adolescent girls but when seen from the results , young women who have a history of abnormal menstrual risk 1.3 times more likely to develop anemia than girls who have a normal menstrual history .